Neighbourhood Ecologies Creative Ethnographies of Urban Environments - Vanni, Ilaria; Crosby, Alexandra (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2025)
XVII, 159 p. 23 illus., 20 illus. in color.